An examination of motor unit firing rates during steady torque of maximal efforts with either an explosive or slower rate of torque development - Reece, T. M.; Arnold, C. E.; Herda, T. J. (Experimental Physiology, 2021)
What is the central question of this study? The aim was to explore agonist and antagonist motor unit firing rates during maximal efforts performed with either an explosive or a slower rate of torque development.